Evaluating optical nonlinearities and applications of photonic nanomaterials - SILVA NETO, Manoel Leonardo da (2021)
The development of new materials is crucial for applications in various areas. In this sense, nanomaterials in their most diverse types, shape, and size have been synthesized. The miniaturization of materials where at least one dimension is below 100 nm brings interesting properties, which significantly increases their applicability. In this work we investigated the nonlinear optical properties of the four types of materials: Transition Metal Dichalcogenides (TMD’s), Gold Nanoclusters (AuNC’s), Graphene Quantum Dots (GQD’s), and NaNbO3 nanocrystals, using the techniques of Z-Scan, and Hyper-Rayleigh Scattering (HRS) and a random laser application was performed. Interesting properties have been found in TMD’s. A high value for the first hyperpolarizability of ZrTe2 monolayers suspended in acetonitrile (ACN) was measured using the HRS technique, and a dipolar behavior for the nonlinear polarization was demonstrated. It was characterized for the first time the nonlinear refraction index of ZrTe2 monolayers suspended in ACN and, as an application of this material, we used it as a scatter for random laser. In NbS2 monolayers suspended in ACN, a change in the signal of the nonlinear refraction index from negative to positive and the transition from two-photons absorption to a saturated behavior with the increase of intensity was shown. In MoS2 monolayers, the fifth-order nonlinear refraction index was demonstrated for the first time. In MGC’s with six atoms (Au6(GSH)2(MPA)2) dissolved in water, the first hyperpolarizability was characterized using the HRS technique. Increase of the hyperpolarizability with decrease in the number of atoms, already demonstrated in the literature, was also seen in this work. For two different GQD’s, the first hyperpolarizability was determined applying the HRS technique; a quadrupolar behavior was demonstrated from polarization measurements. Also, for GQD’s the two-photon absorption cross-section was characterized by two-photon induced luminescence. Finally, NaNbO3 nanocrystals prepared using different synthesis temperatures were characterized applying the HRS technique. An increase in the first hyperpolarizability with temperature was observed.